Pengaruh Motivasi, Pengalaman, dan Pengembangan Karir Terhadap Kinerja Karyawan PT. Wira Sandi di Binus Serpong - Silviana Naila; Bambang Mardisentosa; Hani Hasanah (MANAJEMEN, 2025)
This study was conducted to determine the influence of motivation, experience, and career development on employee performance at Binus Serpong. The method used was a quantitative approach with primary data collection through the distribution of closed-ended questionnaires using a Likert scale. The population studied was 50 respondents, and all were taken as samples using a saturated sampling method, due to the relatively small number of respondents. Data processing used SPSS version 25 and included various tests. The results of the t-test indicate that motivation contributes positively and significantly to performance. Career development also has a significant influence. However, work experience does not have a significant effect. The F-test resulted in a simultaneous test value that significantly influences performance. Thus, partially, only motivation and career development significantly influence employee performance, while work experience does not. However, together, these three variables are able to explain variations in employee performance significantly.